Boundary Hölder regularity for a class of fully nonlinear elliptic partial differential equations. (March 2022) - Li, You; Li, Mengni
Abstract: We are concerned in this paper with the boundary regularity of solutions to the Dirichlet problem for a class of fully nonlinear elliptic partial differential equations. Constructing delicate sub-solutions leads us to effective boundary regularity estimates of convex solutions to the problem. Emphasis here is on the relation of our boundary regularity result with the convexity of the domain described by an ( a, η ) type.